Rapid identification of enteric bacteria from whole genome sequences using average nucleotide identity metrics - Lindsey, Rebecca L.; Gladney, Lori M.; Huang, Andrew D.; Griswold, Taylor; Katz, Lee S.; Dinsmore, Blake A.; Im, Monica S.; Kucerova, Zuzana; Smith, Peyton A.; Lane, Charlotte; Carleton, Heather A. (Frontiers in Microbiology, 2023)
Identification of enteric bacteria species by whole genome sequence (WGS) analysis requires a rapid and easily standardized approach. We leveraged the principles of Average Nucleotide Identity using MUMmer (ANIm), which calculates the percent bases aligned between two bacterial genomes and their corresponding ANI values, to set threshold values for determining species consistent with the conventional identification methods of known species.The performance of species identification was evaluated with the Reference Genome Dataset v2 (RGDv2), comprised of 43 enteric genome assemblies representing 32 species, and the Test Genome Dataset (TGDv1), comprised of 454 genome assemblies which is designed to represent all species needed to query for identification, as well as rare and closely related species. RGDv2 contains: six Campylobacter spp., three Escherichia/Shigella spp., one Grimontia hollisae, six Listeria spp., one Photobacterium damselae, two Salmonella spp., and thirteen Vibrio spp, and the TGDv1 contains 454 enteric bacterial genomes representing 42 different species. Analysis showed when a standard minimum of 70% genome bases alignment existed, the ANI threshold values determined for these species were ≥95 for Escherichia/Shigella and Vibrio species, ≥93% for Salmonella species, and ≥92% for Campylobacter and Listeria species. Using these metrics, the RGDv2 classified all validation strains in TGDv1 correctly at the species level, consistent with classification based on previous gold standard methods.